Belize's 2016-17 sovereign debt restructuring: Third time lucky? - Tamon Asonuma; Michael G. Papaioannou; Eriko Togo; Bert van Selm (Journal of Banking and Financial Economics (JBFE), 2020)
This paper examines the causes, process, and outcome of Belize's 2016-17 sovereign debt restructuring - its third episode in last 10 years. As was the case in the earlier two restructurings, in 2006-07 and in 2012-13, the 2016-17 debt restructuring was executed through collaborative engagement with creditors outside an IMF-supported program. While providing liquidity relief and partially addressing long-term debt sustainability concerns, the restructuring will need to be underpinned by ambitious fiscal consolidation and growth-enhancing structural reforms to secure durable gains and avoid future debt distress situations.
Keywords: F34; G15; H63; 330; Sovereign Debt; Sovereign Defaults; Sovereign Debt Restructurings; Serial DebtRestructurings; Belize